Virtual learning environment engagement and learning outcomes at a ‘bricks-and-mortar’ university - Boulton, Chris A.; Kent, Carmel; Williams, Hywel T.P. (Computers and education, 2018)
In this study, we analyse the relationship between engagement in a virtual learning environment (VLE) and module grades at a ‘bricks-and-mortar’ university in the United Kingdom. We measure VLE activity for students enrolled in 38 different credit-bearing modules, each of which are compulsory components of six degree programmes. Overall we find that high VLE activity is associated with high grades, but low activity does not necessarily imply low grades. Analysis of individual modules shows a wide range of relationships between the two quantities. Grouping module-level relationships by programme suggests that science-based subjects have a higher dependency on VLE activity. Considering learning design (LD), we find that VLE usage is more important in modules that adopt an instruction-based learning style. We also test the predictive power of VLE usage in determining grades, again finding variation between degree programmes and potential for predicting a student's final grade weeks in advance of assessment. Our findings suggest that student engagement with learning at a bricks-and-mortar university is in general hard to determine by VLE usage alone, due to the predominance of other “offline” learning activities, but that VLE usage can nonetheless help to predict performance for some disciplines. •The relationship between VLE engagement and success varies across modules.•High VLE usage linked to high success, but low usage not linked to low success.•VLE usage is more important for instruction-based learning styles.•In some subjects, VLE usage can be used to predict final grade, weeks in advance.•‘Bricks-and-mortar’ engagement cannot be determined by digital traces alone.